Dealing with chemical safety [ (Safetycare series, 1989)
Looks at the ways of handling and using chemicals in the workplace. Stresses the need for a commitment by everyone to follow these safe work procedures and realise the risks and hazards involved. Having an ongoing safety program to reduce accidents will ensure a safer workplace